Targeting Shp2 as a therapeutic strategy for neurodegenerative diseases - Jiao Pang; Changqian Cen; Yuan Tian; Xingrui Cao; Liang Hao; Xueshu Tao; Zhipeng Cao (Translational Psychiatry)
Abstract The incidence of neurodegenerative diseases (NDs) has increased recently. However, most of the current governance strategies are palliative and lack effective therapeutic drugs. Therefore, elucidating the pathological mechanism of NDs is the key to the development of targeted drugs. As a member of the tyrosine phosphatase family, the role of Shp2 has been studied in tumors, but the research in the nervous system is still in a sporadic state. It can be phosphorylated by tyrosine kinases and then positively regulate tyrosine kinase-dependent signaling pathways. It could also be used as an adaptor protein to mediate downstream signaling pathways. Most of the existing studies have shown that Shp2 may be a potential molecular “checkpoint” against NDs, but its role in promoting degenerative lesions is difficult to ignore as well, and its two-way effect of both activation and inhibition is very distinctive. Shp2 is closely related to NDs-related pathogenic factors such as oxidative stress, mitochondrial dysfunction, excitatory toxicity, immune inflammation, apoptosis, and autophagy. Its bidirectional effects interfere with these pathogenic factors, making it a core component of the feedback and crosstalk network between multiple signaling pathways. Therefore, this article reviews the molecular mechanism of Shp2 regulation in NDs and its regulatory role in various pathogenic factors, providing evidence for the treatment of NDs by targeting Shp2 and the development of molecular targeted drugs.